Flow-induced order–order transitions in amyloid fibril liquid crystalline tactoids - Hamed Almohammadi (Nature Portfolio, 2020)
Tactoids are liquid crystal droplets with nearly vanishing interfacial tension. Almohammadi et al. show using a microfluidic focusing device how to manipulate them gently enough to facilitate the study of amyloid liquid crystal phase transitions subject to non-equilibirum forcing and shape changes.